Marketing Strategy For Gold Installment Products in Increasing Customer Interest at Bank Syariah Indonesia: A Systematic Literature Review (2022-2026) - Lutfiya Ardania; Dunuroi Assuryani; Achmad Junaidi (MUQADDIMAH: Jurnal Ekonomi, Manajemen, Akuntansi dan Bisnis, 2026)
Global gold price volatility and high inflation during the 2022–2026 period established gold as a primary safe-haven asset, prompting Bank Syariah Indonesia (BSI) to expand its "Cicil Emas" (Gold Installment) product. Moving beyond fragmented, single-site empirical inquiries, this study offers a novel high level synthesis of 20 peer-reviewed journal articles from Google Scholar and Crossref to formulate a national macro marketing model. Guided by the PRISMA 2020 protocol, the literature selection was systematically processed through a six-stage qualitative thematic analysis, encompassing data familiarization, open coding, theme identification, thematic review, pillar definition, and narrative synthesis. The findings reveal a structural transition toward a "Phygital" marketing framework. BSI resolves digital trust deficits by integrating BYOND mobile application efficiency with physical branches acting as institutional trust anchors. Additionally, ethical positioning under Sharia principles mitigates price sensitivity through spiritual certainty, while operational velocity in gold appraisal and direct outreach via canvassing convert public awareness into concrete investment decisions. This synthesis bridges localized empirical gaps, establishing a comprehensive strategic reference for global Islamic banking governance.